Metaheurísticas aplicadas na sintonia de controladores PID: estudo de casos - Souza, João Olegário de Oliveira de (Universidade do Vale do Rio dos Sinos, 2013)
The Proportional, Integral and Derivative controllers, commonly called PID controllers, are widely used in industrial process control, in both SISO and multivariable systems. Today about 95% of controllers use this type of structure in the industry. The big problem is that most of them are poorly tuned, in many cases compromising the performance of industrial loops. This work presents a general review on nature-inspired algorithms, Simulated Annealing and Genetic Algorithms (basement, characteristics, parameters, operators) and its application in the problem of tuning PID controllers in both single variable and multivariable systems. There will be through case studies, a comparative analysis of these metaheuristics with established methods in the literature in conventional industrial applications using as evaluation function the Integral of time multiplied by the Absolute Error (ITAE) index. The work also proposes the study of PID controllers using multiobjective genetic algorithms which meet two performance criteria: overshoot and the Integral Time Square Error (ITSE) index. The results obtained confirm that Genetic Algorithms are an effective and reliable method to optimize complex problems.
Keywords: Controladores PID; Algoritmos genéticos; Simulated annealing; Otimização; Inteligência artificial; PID control; Genetic algorithms; Optimiztion; Artificial intelligence; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação